Criminal Law Enforcement against Illegal Nickel Ore Mining (A Case at Resort Police of Kolaka Utara) - Jamarin Riche (Al-'Adl, 2021)
The crime of illegal nickel ore mining is a crime in the mining business carried out by individuals, groups of people, or companies/foundations with legal entities in which their operations do not have a legal permit from government agencies based on the applicable regulations threatened by the criminal sanctions for anyone who violates the prohibition. Article 38 of Law Number 3 of 2020 concerning Mineral and Coal Mining states that “Mining business actors include business entities, cooperatives, and Individuals." Accordingly, mining actors can be grouped with large-scale mining, medium-scale mining, and small-scale mining in the form of community mining. This research used an empirical legal research method to obtain primary data through observation and interviews in Sulawesi Tenggara related to the enforcement of criminal law against illegal nickel ore mining (a case study at the regional police of Kolaka Utara). With the change in the legislation regarding mining itself, the government with the Regional Police of Sulawesi Tenggara must have controlled and eradicated the illegal mining that occurred in Sulawesi Tenggara, included Kolaka Utara. Accordingly, the research problems are 1. What are the police efforts regarding the law enforcement for the criminal act of illegal nickel ore mining at the regional office of Sulawesi Tenggara? 2. What are the factors that hinder the police in enforcing the criminal act of illegal nickel ore mining? Law enforcement is an attempt to bring the ideas of justice, legal certainty, and social benefits into reality. Law enforcement is essentially a process of an embodiment of ideas. Enforcement is the process of making efforts to establish or functioning the legal norms as guidelines in legal relations in social and state life.